PADANAN KOSAKATA ARAB DALAM AL-QUR'AN TERJEMAH VERSI INDONESIA DAN MALAYSIA - Astari, Rika; Yusroh, Yusroh; Malik, Abdul; bin Sapar, Ahmad Arifin; Putrisari, Nurina Dyah (Arabi : Journal of Arabic Studies, 2020)
The purpose of this study is to describe the differences in the concept of meaning between the translation of the Qur'an in the Indonesian and Malaysian versions and explain the factors that influence the differences in the concept of meaning. This is a qualitative study that employs library material analysis with enrichment from the interview. Several material objects used, such as the Al-Wafi  dictionary and Diwan dictionary, the quranic verses about women in the Malaysia Team of Islamic Progress (JAKIM), and Ministry of Religion RI in January 2017.  The difference in its meaning was analyzed by lexical decomposition.  It was concluded that the concept meaning of a word in Malaysian tends to be used in various contexts and has polysemy. The factors that influence of distinguishing in meaning concept are social, cultural, political, government policies. The translation of the Quran in the Malay language version tends to use the majazi expression and is more textual. The Indonesia translation of the Qur'an more contextual due to the influence of Islamic thought in Indonesia, which more moderate, tolerant, and accommodate local wisdom.